2006
DOI: 10.1073/pnas.0510031103
|View full text |Cite
|
Sign up to set email alerts
|

TAF7: A possible transcription initiation check-point regulator

Abstract: Transcription consists of a series of highly regulated steps: assembly of a preinitiation complex (PIC) at the promoter nucleated by TFIID, followed by initiation, elongation, and termination. The present study has focused on the role of the TFIID component, TAF7, in regulating transcription initiation. In TFIID, TAF7 binds to TAF1 and inhibits its intrinsic acetyl transferase activity. We now report that although TAF7 remains bound to TAF1 and associated with TFIID during the formation of the PIC, TAF7 dissoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(73 citation statements)
references
References 41 publications
(45 reference statements)
3
65
0
5
Order By: Relevance
“…S7) as follows. As a component of TFIID, TAF7 inhibits the TAF1 AT activity until PIC assembly is complete, thereby preventing premature initiation (27). Upon completion of PIC assembly, TAF7 is released from TAF1, allowing transcription to initiate with the first phosphodiester bond formation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…S7) as follows. As a component of TFIID, TAF7 inhibits the TAF1 AT activity until PIC assembly is complete, thereby preventing premature initiation (27). Upon completion of PIC assembly, TAF7 is released from TAF1, allowing transcription to initiate with the first phosphodiester bond formation.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, MHC class I transcription is inhibited both in vitro and in vivo by the viral transactivator, HIV Tat, which binds to the TAF1 AT domain, inhibiting its enzymatic activity (22,23). TAF7, a cellular 55-kDa TFIID component (24,25), also binds to TAF1 inhibiting its AT activity and repressing MHC class I transcription (26) Significantly, we have demonstrated that TAF7 remains bound to TAF1/TFIID until PIC assembly is complete, whereupon it is released enabling transcription initiation and elongation (27). Thus, TAF7 is an intrinsic regulator of transcription.…”
mentioning
confidence: 84%
See 3 more Smart Citations